2018
DOI: 10.4085/1062-6050-339-17
|View full text |Cite
|
Sign up to set email alerts
|

A 9-Year Epidemiologic Study (2007–2015) on Race-Day Jockey Fall and Injury Incidence in Amateur Irish Horse Racing

Abstract: Context Point-to-point racing may place jockeys at risk of serious injuries due to the high incidence of falls as previously reported. Despite many advances in health and safety strategies, the incidence of falls and injuries in point-to-point racing has not been reported since 2006. Objectives To provide a longitudinal analysis of the fall and injury incidence in point-to-point horse racing jockeys in Ireland from 2007 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…This was similar to findings in Australia, Ireland and New Zealand where less experienced jockeys or apprentices (classified by number of career rides) had higher fall rates than professional jockeys. 15,16,21 In the United Kingdom, horses have a lower risk of fatal limb fracture when ridden by more experienced jockeys 22 and amateur jockeys have a higher rate of falls and fracture incidence than professional jockeys in Ireland point to point (jumps) racing. 15 Apprentice jockeys were only associated with jockey falls in steeplechase racing.…”
Section: Flat Racingmentioning
confidence: 99%
See 2 more Smart Citations
“…This was similar to findings in Australia, Ireland and New Zealand where less experienced jockeys or apprentices (classified by number of career rides) had higher fall rates than professional jockeys. 15,16,21 In the United Kingdom, horses have a lower risk of fatal limb fracture when ridden by more experienced jockeys 22 and amateur jockeys have a higher rate of falls and fracture incidence than professional jockeys in Ireland point to point (jumps) racing. 15 Apprentice jockeys were only associated with jockey falls in steeplechase racing.…”
Section: Flat Racingmentioning
confidence: 99%
“…15,16,21 In the United Kingdom, horses have a lower risk of fatal limb fracture when ridden by more experienced jockeys 22 and amateur jockeys have a higher rate of falls and fracture incidence than professional jockeys in Ireland point to point (jumps) racing. 15 Apprentice jockeys were only associated with jockey falls in steeplechase racing. Apprentice and amateur riders were associated with jockey falls in jumps racing in Ireland and both flat and jumps racing in Australia.…”
Section: Flat Racingmentioning
confidence: 99%
See 1 more Smart Citation
“…Jockeys with low racing workloads likely supplement their work as jockeys with extra track work (daily exercise of race horses) or stable-hand duties, as occurs with failed apprentices in Britain [18,20]. Due to their low workload, they are likely also to be inexperienced in race day riding, which has been linked to horse performance [21,22]. It has been identified that riding a race is more physically demanding than riding daily track work [23] and jockeys rarely participate in additional off-horse physical training regimes except as a measure to reduce weight [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…2 A single misstep or slight error may result in the jockey being thrown from the horse, potentially resulting in catastrophic injury or death. 2 While most reported injuries have been associated with falls, [3][4][5][6][7] there are also injuries that can result from training activities or simply being in close proximity to a horse. 8 Professional horse racing requires jockeys to train year-round and compete at high levels in front of millions of viewers, yet they are often under-recognised as athletes, particularly in the USA.…”
Section: Introductionmentioning
confidence: 99%